Smear layer removal with citric acid solution - Petrović Violeta; Živković Slavoljub (Serbian Medical Society - Dental Section, Belgrade, 2005)
The aim of this study was to evaluate efficacy in smear layer removal of 17% EDTA and 10% citric acid, using SEM. Material and method: Twenty human, extracted teeth with a single root canal were examined. Whilst instrumentation with step-back technique and manual K files, root canals were irrigated with 2 ml of 2.5% NaOCl, between each file size. After instrumentatio n, specimens were divided into two groups. The first group was irrigated with a final flush of 17% EDTA, during one minute, and the second group was irrigated with a 10% citric acid. Results: Irrigation with 17% EDTA and 10% citric acid removed smear layer from the root canals walls. There was not statistically significant differences (p>0.05) in cleaning ability between EDTA and citric acid groups.